The Influence of Perception of Tastura Cultural Value Integration and Compliance with Sharia Principles in the Profit Sharing System on the Decision to Become a Member of the Merah Putih Cooperative in Central Lombok - Supratman Supratman; Galih Mulya Subastyan (al-Afkar, Journal For Islamic Studies, 2026)
Cooperatives play an important role as economic institutions in improving community welfare through principles of mutual cooperation and member empowerment. In societies with strong local cultural values and a predominantly Muslim population, the integration of local cultural values and compliance with sharia principles in cooperative management can influence people’s decisions to become members. This study aims to analyze the effect of perceptions of the integration of Tastura cultural values and compliance with sharia principles in the profit-sharing system on the decision to become members of the Koperasi Merah Putih in Central Lombok. This research uses a quantitative approach with a total sampling technique involving 72 respondents who are cooperative members. Data were collected through questionnaires and analyzed using multiple linear regression after passing validity, reliability, and normality tests. The results show that perceptions of the integration of Tastura cultural values and compliance with sharia principles have a significant effect both partially and simultaneously on the decision to become cooperative members. These findings indicate that the integration of local cultural values and the consistent implementation of sharia principles can increase public trust in cooperatives and encourage membership participation. Therefore, strengthening local cultural values and maintaining consistency in implementing sharia principles in cooperative management are important strategies to enhance community participation in cooperatives.